PATU11 IL2RA and CD226 genotypes influence multiple sclerosis disease outcome. Issue 11 (22nd October 2010) - Mihalova, T; Ban, M; Baker, A; Abraham, R; Strange, R; Hawkins, C P
Abstract : Introduction: MS is a chronic inflammatory disorder of the central nervous system. Whole genome analysis has identified discrete chromosomal regions outside the most powerfully associated MHC region that might harbour susceptibility genes: IL2RA, IL7R, TYK2, CD226 and CLEC16. 1–4 Genetic heterogeneity is likely to contribute to variability in MS outcome. Methods: We examined nine single nucleotide polymorphisms (SNPs) in eight genes in 742 MS with MS severity score being used as the disease outcome using linear regression statistical analysis (STATA). Results: Mutant allele (GG) of SNP rs2104286, in gene IL2RA on chromosome 10p15, was associated with better disease outcome: p=0.004, coefficient=−1.23, 95% CI −2.1 to −0.4. Wild type allele (CC) of SNP rs763361, in gene CD226 on chromosome 18q22.3, was associated with better disease outcome: p=0.002, coefficient=−0.86, 95% CI −1.4 to −0.33. We detected no significant impact on disease outcome for the remaining 7 SNPs. Discussion: We have demonstrated that polymorphism in IL2RA and CD226 genes appears to have significant influence on the disease outcome in our MS population. As novel therapies become more widely available for treatment of MS, risk assessment and response to therapy could soon be influenced by detailed genotype analysis in individual patients.